Lean auditing : driving added value and efficiency in internal audit - Paterson, James C., 1963- (Chichester, West Sussex, United Kingdom : Wiley, 2015)
"'How can you argue with the core principles of Lean, that you focus on what provides value to your customer and eliminate work that is not necessary (muda)? Internal auditors need to understand not only who their primary customers are, but what is valuable to them - which in most cases is assurance that the risks that matter to the achievement of objectives are properly managed. We need to communicate what they need to know and not what we want to say. This incessant focus on the customer and the efficient production of a valued product should extend to every internal audit team. How else can we ensure that we optimize the use of our limited resources to address the dynamic business and risk environment within which our organizations operate?'Norman Marks, GRC Thought Leader. Using lean techniques to enhance value add and reduce waste in internal auditing. Lean Auditing is a practical guide to maximising value and efficiency in internal audit through the application of lean techniques. It is an ideal book for anyone interested in understanding what progressive, value adding audit can be like. It is also ideal for anyone wondering whether audit activities can be streamlined or better co-ordinated with other activities. The book contains practical advise from the author's experience as CAE of AstraZeneca PLC; from his work as a consultant specializing in this field; as well as insights from leading CAEs in the UK, US and elsewhere. In addition, there are important insights from thought leaders such as Richard Chambers (IIA US) and Norman Marks (GRC thought leader) and Chris Baker (Technical Manager of the IIA UK). Increasing pressure on resources is driving a need for greater efficiency in all areas of business, and Internal Audit is no exception. Lean techniques can help streamline the workflow, but having only recently been applied to IA, lack the guidance available for other techniques. Lean Auditing fills this need by combining expert instruction and actionable advice that helps Internal Auditors: Benchmark their efficiency against lean ways of working Understand warning signs of waste and lower added value Understanding practical ways of working that improve added value and reduce waste Gain confidence about progressive ways of working in internal audit Understand how improved ways of working in audit can positively impact the culture of the wider organization. One of the keys to the lean audit is finding out exactly what the stakeholder wants, and eliminating everything else. Scaling back certain operations can delineate audit from advisory, and in the process, dramatically improve crucial outcomes. To this end, Lean Auditing is the key to IA efficiency"--publisher's description.
A "Value Gap" between the Perceptions of Audit and StakeholdersThe Importance of Paying Attention to Dissatisfiers; RECOMMENDED PRACTICES; Make a Commitment to Adding Value beyond Motherhood and Apple Pie; Strive to Clarify What Adds Value and What Does Not; Identify Different Perceptions of Value and Develop a Plan to Address the Most Problematic Areas; DELIVER VALUE TO MULTIPLE STAKEHOLDERS -- BUT MANAGE BOUNDARIES; The Delivery of Value should Always Take into Account Cost; Delivering Delighters is Often Simpler than You Think; Listen, and Respond, to the "Voice of the Customer."
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Auditing, Internal; Auditing, Internal; Auditing; Financial statements; BUSINESS & ECONOMICS -- Auditing; Auditing, Internal; Electronic books